1998
DOI: 10.1002/pdi.1960150408
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of treatments available for the management of Type 2 diabetes: Results from an international survey of physicians

Abstract: This is the second paper presenting information from a prospective, cross‐sectional survey of patients with Type 2 diabetes in France, Germany and the UK. An anonymised physician‐completed diary card was used to collect data about the treatment of 3,043 drug‐treated patients with Type 2 diabetes. The most common antidiabetic treatment, taken by 48% of patients aged over 60 years, was sulphonylurea monotherapy. The most frequent combination was a sul‐phonylurea with a biguanide. Nearly 40% of patients who had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, most patients eventually require exogenous insulin injections to attain glycemic control targets (1). Despite this, patients and physicians appear to be hesitant to use insulin, and, consequently, patients remain in poor glycemic control (2)(3)(4)(5). Needle anxiety is one of the factors associated with this reluctance (6,7); therefore, new routes of insulin administration could be used to achieve and maintain optimal glycemic control.…”
mentioning
confidence: 99%
“…However, most patients eventually require exogenous insulin injections to attain glycemic control targets (1). Despite this, patients and physicians appear to be hesitant to use insulin, and, consequently, patients remain in poor glycemic control (2)(3)(4)(5). Needle anxiety is one of the factors associated with this reluctance (6,7); therefore, new routes of insulin administration could be used to achieve and maintain optimal glycemic control.…”
mentioning
confidence: 99%
“…Worldwide studies have shown that hyperglycemia is a symptom of metabolic disorders like diabetes. In recent years the treatment goal is focused on rectifying the metabolic state and lowering the risk of micro and macrovascular complications as well [8].…”
Section: Introductionmentioning
confidence: 99%